2020
DOI: 10.1007/s10646-020-02182-8
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid impairs performance on a model flower handling task in bumblebees (Bombus impatiens)

Abstract: Bumblebees exposed to neonicotinoid pesticides collect less pollen on foraging trips. Exposed bumblebees are also slower to learn to handle flowers, which may account for reduced pollen collection. It is unclear, however, why neonicotinoid exposure slows learning to handle flowers. I investigated the effect of imidacloprid, a neonicotinoid pesticide, on bumblebee motor learning using a lab model of flower handling. Bumblebees learned to invert inside a narrow tube and lift a petal-shaped barrier to reach a rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 160 publications
0
6
0
Order By: Relevance
“…Studies with similar experimental setup have shown results alike ours (e.g., Gill et al 2012;Gill & Raine 2014;Feltham et al 2014;Stanley et al 2015a;Samuelson et al 2016). Decrease in foraging effectiveness has been attributed to several different mechanisms, ranging from learning and memory impairment (Stanley et al 2015a;Samuelson et al 2016), chronic behaviour impairment (Gill & Raine 2014) and reduction in flower handling efficiency (Phelps et al 2020). However, as we did only measure the foraging bout duration, we are unable to determine the exact cause for the extended foraging bouts.…”
Section: Foraging Bout Durationmentioning
confidence: 54%
“…Studies with similar experimental setup have shown results alike ours (e.g., Gill et al 2012;Gill & Raine 2014;Feltham et al 2014;Stanley et al 2015a;Samuelson et al 2016). Decrease in foraging effectiveness has been attributed to several different mechanisms, ranging from learning and memory impairment (Stanley et al 2015a;Samuelson et al 2016), chronic behaviour impairment (Gill & Raine 2014) and reduction in flower handling efficiency (Phelps et al 2020). However, as we did only measure the foraging bout duration, we are unable to determine the exact cause for the extended foraging bouts.…”
Section: Foraging Bout Durationmentioning
confidence: 54%
“…The damage of neonicotinoids on bees, bumblebees and other species of beneficial insects has now been confirmed by many other studies (Long & Krupke, 2016;Arce et al, 2017;Phelps et al, 2020).…”
Section: On Bees and Batsmentioning
confidence: 67%
“…The negative fitness effects of neonicotinoid insecticide ingestion have been well documented in bees, but more work is needed to examine neonicotinoid effects across a broader range of non‐target insects. In bees, at low concentrations (<50 ng/mL, readily found in field samples) bees suffer from reduced foraging efficiency and poor nutritional status (Azpiazu et al, 2019; Feltham, Park, & Goulson, 2014; Lämsä, Kuusela, Tuomi, Juntunen, & Watts, 2018; Morfin, Goodwin, Correa‐Benitez, & Guzman‐Novoa, 2019; Phelps, Strang, & Sherry, 2020; Scholer & Krischik, 2014; Stanley & Raine, 2016; 2017). There is also evidence for low‐dose effects on bee social behaviour, reproduction, navigation and flight performance (Bryden, Gill, Mitton, Raine, & Jansen, 2013; Crall et al, 2018; Fischer et al, 2014; Laycock, Lenthall, Barratt, & Cresswell, 2012; Scholer & Krischik, 2014; Switzer & Combes, 2016; Tosi, Burgio, & Nieh, 2017; Whitehorn, Wallace, & Vallejo‐Marin, 2017).…”
Section: Introductionmentioning
confidence: 99%